2022
DOI: 10.3390/life12091443
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for Identification and Prediction of Toxic Organic Compounds Using Daphnia magna Transcriptomic Profiles

Abstract: A wide range of environmental factors heavily impact aquatic ecosystems, in turn, affecting human health. Toxic organic compounds resulting from anthropogenic activity are a source of pollution in aquatic ecosystems. To evaluate these contaminants, current approaches mainly rely on acute and chronic toxicity tests, but cannot provide explicit insights into the causes of toxicity. As an alternative, genome-wide gene expression systems allow the identification of contaminants causing toxicity by monitoring the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Diéguez et al 23 reported linear and nonlinear QSAR modeling approaches for the prediction of the acute toxicity of pesticides towards Americamysis bahia , and they have reported that the Random Forest (RF) regression model was a superior model having R 2 = 0.812, lower values of RMSE = 0.595, and MAE = 0.462 in the cross-validation training set, and also similar values for the external validation set. Choi et al 24 reported different machine-learning models for the identification and prediction of toxic organic compounds using Daphnia magna transcriptomic profiles. From their work, they have concluded that a combination of feature selection based on feature ranking and a random forest classification algorithm had the best model performance, with an accuracy of 95.7%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diéguez et al 23 reported linear and nonlinear QSAR modeling approaches for the prediction of the acute toxicity of pesticides towards Americamysis bahia , and they have reported that the Random Forest (RF) regression model was a superior model having R 2 = 0.812, lower values of RMSE = 0.595, and MAE = 0.462 in the cross-validation training set, and also similar values for the external validation set. Choi et al 24 reported different machine-learning models for the identification and prediction of toxic organic compounds using Daphnia magna transcriptomic profiles. From their work, they have concluded that a combination of feature selection based on feature ranking and a random forest classification algorithm had the best model performance, with an accuracy of 95.7%.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20] There has been no QSAR work reported previously on toxicity assessment of pesticides (prediction of maximum acceptable daily intake) specically against humans but some similar studies focusing on pesticide risk assessment embodying similar objectivesexploring less toxic and safer pesticides, though without specically targeting their MADIwere previously reported. 15,[21][22][23][24][25][26][27][28][29][30][31][32] These studies include, for example, several diverse indicator speciescrucial for better understanding the toxicity of the pesticide in different ecosystems, pesticidal mechanisms, and so forth, utilizing either linear or machine learning (ML) non-linear models. However, some of the previous studies reported neither different internal and external validation metrics nor mechanistic interpretations.…”
Section: Introductionmentioning
confidence: 99%
“…To predict the toxicity DT [ 42 ] 2 2022 LVQ; RF, and SVML 95.7% 22 toxic organic compounds which includes herbicides, pesticides, and industrial chemicals This approach allows them to thoroughly evaluate the performance of each family and reduce the chances of bias or overfitting. Additionally, by repeating the cross-validation process three times, they can ensure the robustness and reliability of their results RF [ 44 ] 3 2023 RF, ANN, and SVR 7858 compounds were chosen from a pool of 9403 chemicals. ToxCast Database of the US EPA The study selected the chemical bonds (CBs) of 216 compounds using RF, outperforming ANN and SVF models.…”
Section: Resultsmentioning
confidence: 99%
“…ML can be used to predict the toxicity of pesticides and assess their potential risk to human health [ 28 , [42] , [43] , [44] ]. These methods can analyze a wide range of data, such as chemical properties and molecular structures, to identify the patterns and relationships between pesticides and their toxicity levels.…”
Section: Introductionmentioning
confidence: 99%